2016
DOI: 10.1073/pnas.1617460113
|View full text |Cite
|
Sign up to set email alerts
|

Identifying species of symbiont bacteria from the human gut that, alone, can induce intestinal Th17 cells in mice

Abstract: Th17 cells accrue in the intestine in response to particular microbes. In rodents, segmented filamentous bacteria (SFB) induce intestinal Th17 cells, but analogously functioning microbes in humans remain undefined. Here, we identified human symbiont bacterial species, in particular Bifidobacterium adolescentis, that could, alone, induce Th17 cells in the murine intestine. Similar to SFB, B. adolescentis was closely associated with the gut epithelium and engendered cognate Th17 cells without attendant inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
301
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(308 citation statements)
references
References 72 publications
(93 reference statements)
5
301
1
1
Order By: Relevance
“…Although Crohn’s disease was initially characterized as a Th1- and UC as a Th2-driven inflammatory disease, additional T cell subsets have been identified to play a role in IBD mucosal barrier immunity including regulatory T cells and IL-23 responsive Th17 cells (15). In mouse models, human microbiota have been shown to play a critical role in regulating Th1 (19), regulatory T cells (20), and Th17 (16, 21). Immune cell analyses in FMT studies have been limited, but a recent analysis in Crohn’s disease revealed a borderline increase in CD25+ CD127 lo CD4+ T cells at 12 weeks post-FMT (17).…”
Section: Discussionmentioning
confidence: 99%
“…Although Crohn’s disease was initially characterized as a Th1- and UC as a Th2-driven inflammatory disease, additional T cell subsets have been identified to play a role in IBD mucosal barrier immunity including regulatory T cells and IL-23 responsive Th17 cells (15). In mouse models, human microbiota have been shown to play a critical role in regulating Th1 (19), regulatory T cells (20), and Th17 (16, 21). Immune cell analyses in FMT studies have been limited, but a recent analysis in Crohn’s disease revealed a borderline increase in CD25+ CD127 lo CD4+ T cells at 12 weeks post-FMT (17).…”
Section: Discussionmentioning
confidence: 99%
“…These now include protozoans such as Tritrichomonas spp 67, 68 . and a human isolate of Bifidobacterium adolescentis 69 . While single agents are being implicated, it is also highly likely that more complex communities of multiple agents will likely have equally important, if not more important, roles in model phenotypes 70 .…”
Section: Segmented Filamentous Bacteria (Sfb) and Reproducibilitymentioning
confidence: 99%
“…For example, Th17 cells accumulate in the gut and take its role as the safeguards there by secreting cytokines like IL-17 and IL-22, and inducing some antimicrobial peptides and tight junction proteins from intestinal epithelial cells [17][18][19]. Both segmented filamentous bacteria (SFB) from mice's gut [20][21][22] and B. adolescentis from human' [23] could induce T Helper 17 cells (Th17). Not surprisingly, gut microbiota-derived products, such as short-chain fatty acids (SCFAs), adenosine triphosphate (ATP) and various cytokines could also regulate the immune cells and immune response directly or indirectly [23].…”
Section: Cross Talksmentioning
confidence: 99%
“…Both segmented filamentous bacteria (SFB) from mice's gut [20][21][22] and B. adolescentis from human' [23] could induce T Helper 17 cells (Th17). Not surprisingly, gut microbiota-derived products, such as short-chain fatty acids (SCFAs), adenosine triphosphate (ATP) and various cytokines could also regulate the immune cells and immune response directly or indirectly [23]. For instance, excessive production and accumulation of SCFAs such as acetic acid, propionic acid and butyric acid, cause the increased luminal carbohydrates malabsorption and poor gastrointestinal motility, and ultimately might lead to the necrotizing enterocolitis, especially premature infants, whose immune systems are not fully established.…”
Section: Cross Talksmentioning
confidence: 99%
See 1 more Smart Citation